Enantioselective synthesis of (S)‐naproxen using immobilized lipase on chitosan beads. Issue 6 (19th April 2017) - Gilani, Saeedeh L.; Najafpour, Ghasem D.; Heydarzadeh, Hamid D.; Moghadamnia, Aliakbar
Abstract: S‐naproxen by enantioselective hydrolysis of racemic naproxen methyl ester was produced using immobilized lipase. The lipase enzyme was immobilized on chitosan beads, activated chitosan beads by glutaraldehyde, and Amberlite XAD7. In order to find an appropriate support for the hydrolysis reaction of racemic naproxen methyl ester, the conversion and enantioselectivity for all carriers were compared. In addition, effects of the volumetric ratio of two phases in different organic solvents, addition of cosolvent and surfactant, optimum pH and temperature, reusability, and inhibitory effect of methanol were investigated. The optimum volumetric ratio of two phases was defined as 3:2 of aqueous phase to organic phase. Various water miscible and water immiscible solvents were examined. Finally, isooctane was chosen as an organic solvent, while 2‐ethoxyethanol was added as a cosolvent in the organic phase of the reaction mixture. The optimum reaction conditions were determined to be 35 °C, pH 7, and 24 h. Addition of Tween‐80 in the organic phase increased the accessibility of immobilized enzyme to the reactant. The optimum organic phase compositions using a volumetric ratio of 2‐ethoxyethanol, isooctane and Tween‐80 were 3:7 and 0.1% ( v /v/v), respectively. The best conversion and enantioselectivity of immobilized enzyme using chitosan beads activated by glutaraldehyde were 0.45 and 185, respectively. Abstract :